Cultural Conflict Related to Ankara’s Housing Problem - Nazan Kirci (International Journal of Architectural Engineering Technology, 2014)
This study assesses reflections of the structure of culture that is in search of integrity in the architectural and urban context and follows a number of examples from Ankara in doing so. Ankara’s nomination as the capital of the country was an effort at modernization of Anatolia. Apparently slum areas in Ankara commenced during the modernization process. Contrary to hybridization effects of postmodern globalization, the gap among socio-cultural levels in Turkey is enlarged and has caused deterioration affecting architectural unity. The solution of this problems continue to be urban transformation of slum areas within removal projects or to conceal the disreputable appearance of houses. As a result of interaction between different social groups, individual needs and desires of slum dwellers have changed. Since they are belong to neither rural nor urban culture, the aspiration of low-income groups to become part of the consumption society need to be examined through interdisciplinary studies and appropriate solutions in architecture developed accordingly.